Feasibility and acceptability of a contextualized brief psychological intervention for people with bipolar disorder in rural Ethiopia - Mekdes Demissie; Charlotte Hanlon; Lauren C. Ng; Rosie Mayston; Abebaw Fekadu (Pilot and Feasibility Studies)
Abstract Background There is a very large unmet need for appropriate psychological interventions for bipolar disorder (BD) for use in low- and middle-income countries. We developed a psychological intervention for BD in a primary health care (PHC) setting in Ethiopia using the Medical Research Council’s framework for the Development and Evaluation of Complex Interventions. The aim of this study is to investigate the feasibility, acceptability, and fidelity of this newly developed psychological intervention for BD in a PHC setting in south-central Ethiopia. Method A total of 12 euthymic people with bipolar disorder and five caregivers participated in five 20-min weekly sessions of the psychological intervention. We conducted a mixed-method evaluation, including in-depth qualitative interviews, fidelity ratings of a random selection of 25% of the audio recorded intervention sessions, and self-reported change in symptom severity. We used thematic analysis for qualitative data and descriptive analysis for quantitative data. Results Except for one caregiver, all participants completed all five sessions. Intervention providers and recipients expressed satisfaction with the intervention. Intervention providers reported that the intervention can be feasibly delivered in the PHC setting, although 20 min was considered insufficient. While participants acknowledged the importance of involving caregivers in the intervention, they raised privacy concerns. Intervention providers’ adherence to the manual was moderate. Preliminary findings indicate a reduction in depressive symptoms post-intervention and improvement in providers’ perceived knowledge and skills. Conclusions This contextually developed psychological intervention for bipolar disorder has promising feasibility, acceptability, and potential utility. Further studies should evaluate time considerations and effectiveness. Trial registration The trial was registered on 16 August 2024, retrospectively on the Pan African Clinical Trial Registry database [PACTR202408896160144],  https://pactr.samrc.ac.za/TrialDisplay.aspx?TrialID=31727 .